Lower Extremity Microembolism in Open vs. Endovascular Abdominal Aortic Aneurysm Repair - Toursavadkohi, Shahab; Kakkos, Stavros K.; Rubinfeld, Ilan; Shepard, Alexander (Frontiers in Surgery, 2016)
Abstract: Although previous studies have documented the occurrence of microembolization during abdominal aortic aneurysm (AAA) repair by both open and endovascular approaches, no study has compared the downstream effects of these two repair techniques on lower extremity hemodynamics . In this prospective cohort study, 20 patients were treated with endovascular aneurysm repair (EVAR) (11 Zenith, 8 Excluder 1 Medtronic) and 18 patients with open repair (OR) (16 bifurcated grafts, 2 tube grafts). Pre- and post-operative ankle-brachia! indices (ABls) and toe-brachia! indices (TBls) were measured pre-operatively and on post operative day (POD) 1 and 5. Demographics and pre-op ABls/TBls were identical in EVAR (0.97/0.63) and OR (0.96/0.63) patients (p=0.21). There was a significant decrease in ABls/TBls following both EVAR (0.83/0.52, p=0.01) and OR (0.73/0.39, p=0.003) on POD#1, although this decrease was greater following OR than EVAR (p=0.002). This difference largely resolved by POD #5 (p=0.41). In the OR group, TBls in the limb in which flow was restored first was significantly reduced compared to the contralateral limb (0.50 vs 0.61, p=0.03). In the EVAR group there was also a difference in TBls between the main body insertion side and the contralateral side (0.50 vs 0.59, p=0.02). Deterioration of lower extremity perfusion pressures occurs commonly after AAA repair regardless of repair technique. Toe perfusion is worse in the limb opened first during OR and on the main body insertion side following EVAR suggesting that microembolization plays a major role in this deterioration ..The derangement following OR is more profound than after EVAR on POD#1, but recovers rapidly. This finding suggests that microembolizarion may be worse with OR or alternatively that other factors associated with OR (e.g. the hemodynamic response to surgery with redistribution of flow to vital organs peri-operatively) may play a role